A Comparative Study of Job Satisfaction of DSOs and Senior Coaches - Kanu L. Chauhan; Dr. M. G. Vagh (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
The purpose of this research study was “Comparative study of job satisfaction of DSO and senior coach”. For this research study, DSO and coach of Gujarat state were selected as subjects. In this research study, a total of 66 subjects were selected, 33 D.S. and 33 coach. For this research study, DSO and coach brothers of the age group of 21 to 45 years were selected as subjects. In this research study, a questionnaire designed by Dr. Amar Singh and T. R. Sharma was used to measure job satisfaction. To compare the job satisfaction of DSO and senior coach, the significance of the medians was tested at the 0.05 level by applying the ‘t’ ratio. The conclusion was as follows. No significant difference was found in the job satisfaction of DSO and senior coach.